2017
DOI: 10.1063/1.4978403
|View full text |Cite
|
Sign up to set email alerts
|

Multi-directional electromagnetic vibration energy harvester using circular Halbach array

Abstract: In this paper, a multi-directional electromagnetic vibration energy harvester (EVEH) using the circular Halbach array (HA) is presented based on the Faraday’s law of electromagnetic induction. The circular HA is a specific arrangement of permanent magnets which could concentrate the magnetic field inside the circular array by a certain rule, while reduce the magnetic field outside the circular array to almost zero at the same time. The HA could break through the limitation of the related published vibration en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Qiu et al [ 55 ] experimented using circular Halbach arrays and a moving coil, as shown in Figure 6 . They researched the increase in efficiency by using Halbach arrays, which could operate in multiple directions.…”
Section: Moving Coil Vs Moving Magnetmentioning
confidence: 99%
“…Qiu et al [ 55 ] experimented using circular Halbach arrays and a moving coil, as shown in Figure 6 . They researched the increase in efficiency by using Halbach arrays, which could operate in multiple directions.…”
Section: Moving Coil Vs Moving Magnetmentioning
confidence: 99%
“…However, the utilization of the magnetic circuit is low, resulting in low energy harvesting efficiency. Qiu et al [21] carried out experiments using circular Haarbach arrays and moving coils, studying the application of a Haarbach array to improve magnetic flux utilization efficiency, which can operate in multiple directions. Under excitation at 15.4 Hz and 0.5 g, the energy harvester could generate 7.29 mW of power.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some in-plane Halbach arrays [11][12][13] and cylindrical Halbach arrays [14][15][16][17][18] have been presented and utilized. Qiu [19] and Liu [20,21] designed an electromagnetic energy harvester employing a Halbach array and a coil. The coil, which is attached to the end of the cantilever beam, vibrates and results in the generation of induced voltage.…”
Section: Introductionmentioning
confidence: 99%